2020
DOI: 10.1038/s41598-020-58574-7
|View full text |Cite
|
Sign up to set email alerts
|

Practical application of short-term intensive insulin therapy based on the concept of “treat to target” to reduce hypoglycaemia in routine clinical site

Abstract: the aim is to devise a new short-term intensive insulin therapy (n-Siit) based on the concept of "treat to target" to avoid hypoglycaemia and was applied it to various diabetic state. We determined dosage of 1 basal and 3 bolus "treat" insulin based on "target" blood glucose level and changed each insulin dose by small units (2 units) every day for 2 weeks. We evaluated the effects of N-SIIT in 74 subjects with type 2 diabetes (male 45, female 29, 64.9 ± 16.6 years old, HbA1c 10.4 ± 2.6%). Glargine U300 ("trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…While comparisons with other studies of SIIT are to be interpreted cautiously because of differences between studies in insulin agents and SIIT regimen duration, this rate was lower than reported in other SIIT studies where basal and bolus insulin doses were titrated at the same time (28% to 38.1%). 12,22 Hypoglycaemia incidence was reported as an annual rate in a Canadian study of 4 weeks of SIIT (0.20 hypoglycaemic events per person per year; range 0.0 to 0.62). 7 There were no cases of severe hypoglycaemia in our study or these other SIIT studies (where reported).…”
Section: Discussionmentioning
confidence: 99%
“…While comparisons with other studies of SIIT are to be interpreted cautiously because of differences between studies in insulin agents and SIIT regimen duration, this rate was lower than reported in other SIIT studies where basal and bolus insulin doses were titrated at the same time (28% to 38.1%). 12,22 Hypoglycaemia incidence was reported as an annual rate in a Canadian study of 4 weeks of SIIT (0.20 hypoglycaemic events per person per year; range 0.0 to 0.62). 7 There were no cases of severe hypoglycaemia in our study or these other SIIT studies (where reported).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, physicians often titrate the insulin glargine dosage according to the fasting blood glucose (FBG) level, since appropriate day-to-day blood glucose goals may play an important role in achieving glycaemic control in patients receiving insulin therapy [20]. It should also be noted that there was a wide variation between the FBG values to achieve the recommended HbA1c targets from various organizations.…”
Section: Introductionmentioning
confidence: 99%